Preliminary results of the study of subclinical infections of tick-borne pathogens in bitten humans - G. A. Danchinova; N. A. Lyapunova; E. L. Manzarova; I. S. Solovarov; I. V. Petrova; A. V. Lyapunov; J. Bataa; M. A. Khasnatinov (Acta Biomedica Scientifica, 2018)
Background. Early detection of tick-borne pathogens in blood samples of infected people prevents the disease before clinical manifestations using antibiotic and immunoglobulin treatment. As far as tick-borne diseases are associated with significant activation of innate immune response, the changes in the cytokine profile soon after a tick bite could be used as an indicator of early tick-borne infection. Aims. The goal of this study was to characterize the production of cytokines during first 2-4 days after a tick bite in asymptomatic people infected with tick-borne pathogens. Materials and methods. The infection of tick-borne encephalitis virus, B. burgdorferi sensu lato, A. phagocytophilum and E. chaffeensis / E. muris was detected in blood of bitten humans using appropriate commercial real time RT-PCR and ELISA assays. Concentration of 14 cytokines in plasma of 89 infected and 45 non-infected people was established using quantitative ELISA kits. Results. Between 2nd and 4th days after tick bite, the prevalence and concentration of certain cytokines in blood of infected people significantly differed from those of the control group. Bacterial pathogens exhibited very similar patterns of cytokine profiles with induction of IL-1a, IL-8 и IFN-a and suppression of SOD, IL-1Ra и IL-17A. For virus infection the increased concentrations of IL-1 a, IL-8, IL-10, IL-17A, IFN-y and SOD were detected. The only suppressed cytokine was IL-1Ra receptor antagonist. Conclusions. The results suggest that evaluation of innate immune response between 2nd and 4th days after the tick bite could be a useful tool for evaluation of the risk of tick-borne disease for the humans bitten by ticks.